Citraan Dalam Lirik Lagu Polaris Karya Aimer - Nur Hastuti (KIRYOKU, 2021)
Song lyrics are a pitched arrangement/sequence of words, song lyrics are not as easy as composing an essay, but can be obtained from various inspirations. And broadly, song lyrics are a person's expression of something he has seen, heard or experienced. In expressing his experience, the poet or songwriter performs a play on words and language to create attraction and uniqueness to the lyrics or poetry. An image or image is a word or arrangement of words that can express sensory experiences, such as seeing, hearing, and feeling. Images can make the reader feel as if they see, hear, and feel what the poet experienced. Based on this, the author wants to examine the Polaris song to find out what images / images are in the lyrics of the song